PROGRAM PREVENTIF DAN DETEKSI DINI SKOLIOSIS PADA ORGANISASI SISWA INTRA SEKOLAH DI SMPN 3 SURAKARTA - Dewangga, Mahendra Wahyu; Kinasih, Putri; Farizqi, Kurnia Lutfi; Anggraheni, Anindya Veta; Safira, Chrisnami Ika; Pristianto, Arif (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Kristen Duta Wacana, 2024)
Adolescence is a period of transition from childhood to adulthood. Physically, adolescents experience an increase in body growth, such as an increase in height, as well as the maturity of the organs including the maturity of the reproductive function. Meanwhile, cognitive maturity is identified with the ability to think abstractly. The bad habit of teenagers at school is carrying not a few school supplies, they even carry an extra tote bag to go to school. This if done for a long period of time will result in bad posture or spinal abnormalities. Poor posture results in musculoskeletal problems and leads to postural skoliosis. Many students have complaints of pain and discomfort in the back and waist area, this is caused by sitting in the wrong position for a long time and also many students carry bags that are too heavy and even carry with a tote bag or sling. This can encourage educational activities related to preventive programs and early detection of skoliosis at OSIS SMPN 3 Surakarta. The method we use consists of presentation of material, discussion sessions, exercises and practices. The results obtained after delivering the material were an increase in students' knowledge and increased awareness of the importance of maintaining a good sitting pattern to avoid skoliosis.